The Effectiveness of Micro Learning Design on Storytelling Skills - Hidayat, Arip; Hanifah, Ifah; Rahmatunisa, Wulan; Andriyana , Andriyana (Journal of Ecohumanism, 2024)
Storytelling is an important skill in the world of education that can increase engagement, understanding, and conveying information in a more engaging way. This study aims to test the influence of micro-learning methods on students’ storytelling skills by involving 500 respondents from Sultan Agung Islamic University (Semarang), University of Muhammadiyah Malang (Malang), STIBA-EIC (Jakarta), PGRI University of West Sumatra (Padang), Mataran State Islamic University (Lombok). Respondents were randomly selected from students in the city (30-40 students in each city), with an age range ranging from 19 to 22 years old. The domicile of the respondents came from the city and the surrounding area. The total number of respondents is 500. Of the 500 respondents, 100 respondents (20%) came from students majoring in foreign language colleges, 100 respondents (20%) came from the English language education department, and 300 respondents (60%) came from the Indonesian language and literature education department. The respondents were divided into two groups: experiments that used micro-learning and controls that used traditional methods. The learning design includes the introduction of learning objectives, understanding of storytelling elements, example video analysis, storytelling exercises, as well as recording and feedback. The results of statistical analysis using the Mann-Whitney test showed a significant difference between the two groups, with a significance value of 0.000 (p < 0.05), which indicates that the micro-learning method has a positive and significant influence on improving students’ storytelling skills compared to the traditional method. This indicates that we can reject the null hypothesis (H₀) which states that there is no significant difference between the two groups, and accept the alternative hypothesis (H₁) which states that there is a significant difference. These findings indicate that this approach is not only relevant for language teaching, but can also be adapted to various other forms of learning. With its flexible structure and customizable content, micro-learning can be applied in a variety of disciplines, such as science, mathematics, and art, by utilizing a variety of visual and narrative media.